2023
DOI: 10.1001/jamanetworkopen.2023.17549
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Liver Transplant Referral Among Patients With Cirrhosis at Multiple Safety-Net Hospitals

Abstract: ImportanceA high proportion of underserved patients with cirrhosis receive care at safety-net hospitals (SNHs). While liver transplant (LT) can be a life-saving treatment for cirrhosis, data on referral patterns from SNHs to LT centers are lacking.ObjectiveTo identify factors associated with LT referral within the SNH context.Design, Setting, and ParticipantsThis retrospective cohort study included 521 adult patients with cirrhosis and model for end-stage liver disease–sodium (MELD-Na) scores of 15 or greater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A similarly designed study of multiple safety-net hospitals found low rates of referral (28%) associated with active alcohol use, Black race, uninsured status, and other sociodemographic factors. [4] These results demonstrate significant health care disparities and suggest that a process of prereferral selection is occurring.…”
Section: Second Thoughts About Second Opinions For Liver Transplantationmentioning
confidence: 84%
See 1 more Smart Citation
“…A similarly designed study of multiple safety-net hospitals found low rates of referral (28%) associated with active alcohol use, Black race, uninsured status, and other sociodemographic factors. [4] These results demonstrate significant health care disparities and suggest that a process of prereferral selection is occurring.…”
Section: Second Thoughts About Second Opinions For Liver Transplantationmentioning
confidence: 84%
“…Alcohol-associated liver disease, African-American ethnicity, lower annual income, and western US location were associated with lower rates of these LT outcomes. A similarly designed study of multiple safety-net hospitals found low rates of referral (28%) associated with active alcohol use, Black race, uninsured status, and other sociodemographic factors 4 . These results demonstrate significant health care disparities and suggest that a process of pre-referral selection is occurring.…”
mentioning
confidence: 81%
“…In a recent American observational cohort, including 521 patients with cirrhosis, Yilma M. et al . found a referral rate for LT evaluation of 27.8% (145/521 patients) and an effective transplant rate within a 5-year follow-up period of 5.4% (28/521 patients) [15]. In another recent American observational cohort, including 34 494 patients with cirrhosis, Kanwal F. et al .…”
Section: Discussionmentioning
confidence: 99%
“…study, age ≥70 years and the excess number of comorbidities have also been associated with higher risk for lack of referral for LT evaluation [16]. In other recent American observational cohorts, the following factors were associated with a lower risk of referral for LT assessment: female sex, African-American ethnicity, ALD, active alcohol use or limited sobriety, insurance issues, poor finances, lack of social support, undocumented status, or unstable housing [15–17].…”
Section: Discussionmentioning
confidence: 99%
“…However, because these statistics are based on inpatient data, they may overrepresent etiologies associated with rapid disease progression and acute decompensation, while underrepresenting etiologies with an indolent course. ALD was also the dominant etiology (53.7%), followed by HCV (27.1%), in a multicenter SNH cohort of outpatient referrals for liver transplantation [23]. The liver disease etiologic profile of safety-net patient populations may depend on the clinical context, though ALD and HCV are leading conditions.…”
Section: Epidemiology Of Chronic Liver Disease In Safety-net Populationsmentioning
confidence: 99%